BOBOT TELUR, FERTILITAS, DAYA TETAS DAN BOBOT TETAS TELUR HASIL PERSILANGAN AYAM MERAWANG JANTAN DENGAN AYAM BRESSE BETINA (Eggs weight, fertility, hatchability and hatching weight from crossing merawang rooster and bresse hen) - Lisna Apriliani Rizkiah; Azizah Asma Hamidah; Ichan Pamungkas; Pirda Parida Permadani Pertiwi; Boy Surya Adhitya; Dede Ilpan Kosasih; Seta Astagina; Dewi Wahyuni; Annisa Rahmi; Abdullah Baharun (JURNAL NUKLEUS PETERNAKAN, 2023)
Indonesia have local chicken’s genetic resources and need to be developed as animal protein resource for fulfill market demand and human nutrition. This research aim to analyzed egg weight, fertility, hatchability and hatching weight of local chicken crossed results between Merawang and Bresse chickens. The natural mating method done by put a rooster Merawang with three hens Bresse chickens in a cage. The eggs produced from second until seventh days were collected, then cleaned and put the marker suit to laying eggs time. The marked eggs loaded into an automatic hatching machine (New Karya Mandiri®) with setting of temperature is 36-37°C (60-70% humidity). Eggs fertility determination were did on fifth day incubation with candling method. The parameters observed were weight, fertility, and hatchability the eggs. The results shows the eggs from crossed Merawang rooster and Bresse hen have average eggs weight is 48,33,6 gram, 61,54% fertility, and 62,5% hatchability. The conclusion was the fertility and hatchability of Merawang rooster and Bresse hen crossed (Bresse’s superior chickens UNIDA/BUNIDA F1) through natural mating are still low, while the egg weight and hatching weight produced are not different from other local chickens. as result of crossing Merawang rooster and Bresse hen. BUNIDA F1 chicken have the potential to exploration as a new breed of superior local chickens.